2020
DOI: 10.1016/j.jpsychores.2019.109908
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for posttraumatic stress disorder symptoms induced by medical events: A systematic review

Abstract: Objective: Medical events such as myocardial infarction and cancer diagnosis can induce symptoms of posttraumatic stress disorder (PTSD). The optimal treatment of PTSD symptoms in this context is unknown.Methods: A literature search of 6 biomedical electronic databases was conducted from database inception to November 2018. Studies were eligible if they used a randomized design and evaluated the effect of treatments on medical event-induced PTSD symptoms in adults. A random effects model was used to pool data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
(54 reference statements)
2
15
0
2
Order By: Relevance
“…Psychological treatments may be beneficial in alleviating distress and improving the quality of life of cancer patients (Murray, 2016). Consistent data have demonstrated how TF-CBT, stress management group cognitive-behavioral therapy, and EMDR are able to improve PTSD symptoms more than waitinglist or as usual treatments (Haerizadeh et al, 2020). A metaanalysis including 114 randomized controlled trials showed that TF-CBT and EMDR are the psychological therapies with the strongest evidence of effect for the treatment of PTSD (Lewis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological treatments may be beneficial in alleviating distress and improving the quality of life of cancer patients (Murray, 2016). Consistent data have demonstrated how TF-CBT, stress management group cognitive-behavioral therapy, and EMDR are able to improve PTSD symptoms more than waitinglist or as usual treatments (Haerizadeh et al, 2020). A metaanalysis including 114 randomized controlled trials showed that TF-CBT and EMDR are the psychological therapies with the strongest evidence of effect for the treatment of PTSD (Lewis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More attention and research to key environmental and biological risk factors for PTSD (e.g., childhood adversity, possible biological predisposing factors, including stress-driven activation of biological, and endocrine pathways) that are influential in the maintenance of PTSD and worse patient outcomes (45). With respect to this, further studies are needed to better clarify the role of the serotonin system in the development of PTSS in order to identify women who may be at heightened risk of PTSD amongst breast cancer patients and to properly integrate psychopharmacological and psychological approaches to lessen the negative impact of this chronic mental health condition (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…(Gillies et al, 2016). "La investigación ha demostrado que hacer EMDR no sólo reduce las clasificaciones auto-reportadas de la vivacidad y/o la emocionalidad de los recuerdos autobiográficos desagradables" (Haerizadeh et al, 2019).…”
Section: Discussionunclassified
“…2016; Tribe et al, 2019), como los de ansiedad y de pánico (Acarturk et al, 2016;Gillies et al, 2016;Haerizadeh et al, 2019). Al referir si esta técnica recibe con agrado nuevas hipótesis y métodos, se evidencia en función a los síntomas que presente el paciente (Balbo et al, 2019;Proudlock y Peris, 2020;Schwarz et al, 2019 Resuelve las disputas por medio del experimento o el cálculo.…”
Section: Dominiounclassified